Akty indywidualne z zakresu gospodarowania zasobem mieszkaniowym gminy - Jakubowski, Aleksander (Wydawnictwo Naukowe UAM, 2015)
The management of the municipal housing stock is a way of implementing state housing policy as stipulated in the Constitution (Art. 75). It is handled by municipalities under administrative law and civil law. Individual legislative acts regulating management of hosing stock result in considerable diff erences in judicial decisions delivered in case law. In the resolution of 21st July 2008 (I OPS 4/08), the Supreme Administrative Court conﬁ rmed the two-tier character of proceedings in matters regarding the municipal housing stock: that of administrative law and that of civil law. However, subsequent case law decisions determined that the civil law element prevails. As a consequence, administrative courts ﬁ nd themselves incompetent to review individual acts governing the municipal housing supply. At the same time, courts-of-law do not seem to guarantee any eff ective protection of individuals in such matters. Research has conﬁ rmed that the lettings procedure with regard to renting a ﬂ at from the municipality housing stock consists of two elements. The administrative element covers the issue of the distribution of public property. It comes down to the resolution “whether” to let a particular ﬂ at and the decision “to whom” it can be let . Administering scarce resources is always a public matter. A legislative act issued in such proceedings falls under the competence of the administrative courts and the procedure to be applied is determined by acts of local law and the principal guarantees of procedural fairness which are reﬂ ected in relevant general principles of the Code of Administrative Procedure. The civil law element pertains to negotiations about the content of a lease/rental agreement and the procedure for entering into it, which as such should be reviewed by the courts-of-law. Nevertheless, the conclusion of a valid lease agreement is contingent upon a relevant decision issued by a municipal authority in favour of a given individual.
Individual acts in the ﬁeld of the municipal housing supply
Keywords: housing supply; court competence; two-tier proceedings